Atlas web turístico de la reserva de la biosfera del Archipiélago de San Andrés - Rocha Salamanca, Luz Ángela; Cardenas Contreras, Andrés (Revista Científica, 2007)
In the latest years the web maps has been the most important tool for the dissemination of spatial data, specially in topics like tourism, because this type of maps are more useful than the conventional maps, based on their properties and flexibility. Tools like GIS on line and web cartography provide the elements to create a web atlas in an academic environment, to be useful for dissemination and presentation of spatial data related to tourism. This paper is a result of the research project called "Diseño de un atlas en línea para un sector turístico de Colombia. Caso de estudio San Andrés". The aim of this project was to make a web atlas of the Archipelago of San Andres, Providencia and Santa Catalina, which contributes to increase the number of visitors to the islands, using a methodology that integrates tools like Geographic Information Systems and Information technology. The web atlas design includes: the design of different models, to determine the state of art and knowledge about this topic, data acquisition, filed work on site, and to develop a model for a web map production line, based on internacional standards and applying concepts of GIS on line.